Rapid and Fully Automated Visualization of Subdural Electrodes in the Presurgical Evaluation of Epilepsy Patients - Kovalev, Dimitri; Spreer, Joachim; Honegger, Jürgen; Zentner, Josef; Schulze-Bonhage, Andreas; Huppertz, Hans-Jürgen (American Journal of Neuroradiology, 2005)
Summary: For rapid visualization of subdural electrodes with respect to cortical and subcortical structures, we describe a novel and fully automated method based on coregistration, normalization, optional cerebellum masking, and volume rendering of 3D MR imaging data taken before and after implantation. The key step employs the skull-stripped preimplantation image as a mask to also remove the skull in the postimplantation image. The extracted brain is presented in 3D with the electrodes directly visible by their susceptibility artifacts. Compared with alternative methods, ours is based on freely available software and does not require manual intervention.